Strategi Guru Dalam Mengembangkan Minat Belajar Siswa Pada Mata Pelajaran SKI Melalui Metode Cooperative Script di Kelas III MI Hidayatul Anam Pamekasan - Ach. Khoiril Anam; Akhmad Nurul Kawakip; Ahmad Sholeh (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
Students’ learning interest plays an important role in achieving effective learning outcomes, particularly in Islamic Cultural History (SKI) subjects at the Madrasah Ibtidaiyah level. This study aims to analyze teachers’ strategies in developing students’ learning interest through the implementation of the Cooperative Script method in the third grade of MI Hidayatul Anam Pamekasan. This research employed a qualitative approach with a descriptive design. The research subjects consisted of one teacher and third-grade students selected purposively. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation techniques. The results showed that the teacher’s strategies were implemented through three stages: planning, implementation, and evaluation. In the planning stage, the teacher prepared learning tools adjusted to students’ characteristics. In the implementation stage, the teacher combined the lecture method with the Cooperative Script method to encourage active and participatory learning. In the evaluation stage, the teacher assessed both the learning process and outcomes comprehensively. The application of the Cooperative Script method created an active, interactive, and communicative learning environment, which contributed to increasing students’ learning interest, as reflected in their attention, participation, enthusiasm, and self-confidence. However, challenges such as differences in students’ abilities and limited instructional time were identified. In conclusion, the teacher’s strategy through the Cooperative Script method is effective in enhancing students’ learning interest and can be used as an alternative instructional strategy in SKI learning at the elementary level.